The role of loop gain in predicting upper airway surgical outcomes—what do we know? - Alex, Raichel; Panza, Gino; Mateika, Jason H. (Journal of Thoracic Disease, 2018)
Obstructive sleep apnea (OSA) is a multifactorial disorder characterized by at least three primary phenotypes. The rst phenotype is associated with mechanical impairments of the upper airway leading to increased collapsibility of the upper airway. The second phenotype is defined by a low arousal threshold which contributes to unstable ventilatory control. The third phenotype is defined by a high loop gain which also contributes to unstable ventilatory control during sleep (1,2). Loop gain by definition includes both “plant” (i.e., lung volume, gas exchange rate, circulatory delay) and “controller” (i.e., chemore ex) gain components (3). An overall loop gain of less than 1 is typical of a stable respiratory control system (4). Unfortunately, due to the multitude of phenotypic impairments, optimal treatment for OSA has yet to be established.